Representations of the Post-revolutionary Mexico. Propaganda cinema during the cardenism and the Autonomous Press and Advertising Department (Tzintzun, Revista de Estudios Históricos, 2021)
The present article explores the function of the Autonomous Press and Advertising Department as a creator and transmitter of what the federal government of the post-revolutionary Mexico sought to represent. In order to do so, we will analyze the film corpus produced by this agency, as well as the screening strategies of such films. We will start from the precept that there was a careful selection of the materials shown abroad, which targeted specific audiences. The same way the content of the propaganda films rigorously stuck to the mostimportant points of the political agenda of Lázaro Cárdenas del Río.
Keywords: mexican documentary; propaganda; identity; visual representations; audiovisual memory; nationalism